2001
DOI: 10.1017/s0889189300009115
|View full text |Cite
|
Sign up to set email alerts
|

Perennial wheat: The development of a sustainable cropping system for the U.S. Pacific Northwest

Abstract: Perennial wheat offers a new solution to the long-standing problems of soil erosion and degradation associated with conventional annual small-grain cropping systems in the Pacific Northwest region. Using classical breeding methods, new types of wheat have been developed that maintain the key characteristics of annual wheat, but continue to grow after harvest. Following dormancy in the winter, growth is initiated from the roots or crowns in the spring, allowing a crop to be harvested every fall. By retaining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 12 publications
0
48
1
Order By: Relevance
“…Other, less far-reaching recommendations for reducing soil erosion also involve perennial grains (Wagoner, 1990a;Scheinost et al, 2001). But all of our major grain crops are annuals, and no current perennial species produce sufficiently high yields.…”
Section: The Need For Perennial Grainsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other, less far-reaching recommendations for reducing soil erosion also involve perennial grains (Wagoner, 1990a;Scheinost et al, 2001). But all of our major grain crops are annuals, and no current perennial species produce sufficiently high yields.…”
Section: The Need For Perennial Grainsmentioning
confidence: 99%
“…Suneson et al (1963) reported that their 25 years of work with perennial wheat (Triticum aestivum hybridized with perennial grasses) in California had produced lines whose first-year yields fell "within the range of the lowest yielding commercial wheat varieties" of the time, with a rapid yield decline in subsequent years. Recently, eight intergeneric wheat lines selected for regrowth ability in Washington state, USA yielded between 1600 and 5800 kg/ha, compared with almost 9000 kg/ha for the popular annual wheat cultivar 'Madsen' (Scheinost et al, 2001).…”
Section: B Resource Allocation and Negative Correlationsmentioning
confidence: 99%
See 3 more Smart Citations